Wir Geretteten, ihr Völker: Un’analisi linguistica su liriche scelte di Nelly Sachs - Celeste Catino Geromella (Dive-In, 2025)
The work of Nelly Sachs, Nobel Prize winner for Literature in 1966, is characterized by her aim to express the traumatic experiences of victims and survivors of the genocidal project of Nazism against the Jewish minority. The poet’s voice serves as a megaphone for the suffering of the entire Jewish community and sometimes engages in dialogue with the rest of humanity— both oppressors and bystanders. In this paper, I focus on the linguistic analysis of several works from Nelly Sachs’s early poetic corpus, employing a Critical Discourse Analysis (Van Leeuwen, 1996; Van Dijk, 2001). I used MAXQDA software for coding and analysis, conducting both qualitative and quantitative analyses of the categories of agency and transitivity according to the theory of Systemic Functional Grammar (Halliday 1967; Halliday & Matthiessen 1999, 2004), applied to the German language (cf. Uwe Helm Petersen 2012, 2013). My aim is to outline Sachs’s representation both of self and of the “Other”, to understand a possible evolution of it and of their mutual interactions. The identity of the poet is often expressed and fused in a collective “wir” to include with her the broader victimized Jewish community, as well as the “Other” represents the rest of humanity through the pronoun “ihr”.